The global health system: actors, norms, and expectations in transition. - Nicole A Szlezák (Public Library of Science (PLoS), 2010)
In the first in a series of four articles highlighting the changing nature of global health institutions, Nicole Szlezák and colleagues outline the origin and aim of the series.